Family Shuffling of a Targeted bphA Region To Engineer Biphenyl Dioxygenase - Barriault, Diane (American Society for Microbiology, 2002)
In this work we used a new strategy designed to reduce the size of the library that needs to be explored in family shuffling to evolve new biphenyl dioxygenases (BPDOs). Instead of shuffling the whole gene, we have targeted a fragment of bphA that is critical for enzyme specificity. We also describe a new protocol to screen for more potent BPDOs that is based on the detection of catechol metabolites from chlorobiphenyls. Several BphA variants with extended potency to degrade polychlorinated biphenyls (PCBs) were obtained by shuffling critical segments of bphA genes from Burkholderia sp. strain LB400, Comamonas testosteroni B-356, and Rhodococcus globerulus P6. Unlike all parents, these variants exhibited high activity toward 2,2′-, 3,3′-, and 4,4′-dichlorobiphenyls and were able to oxygenate the very persistent 2,6-dichlorobiphenyl. The data showed that the replacement of a short segment ((335)TFNNIRI(341)) of LB400 BphA by the corresponding segment ((333)GINTIRT(339)) of B-356 BphA or P6 BphA contributes to relax the enzyme toward PCB substrates.